Formulation of Lahuna Leave Extract ( Chromolaena odorata ) and Binahong Leave Extract (Anredera cordifolia) As Antiseptic Ointments - Jumrah, Elfira; Agustina, Ayu Safitri (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2023)
This study utilizes natural ingredients as a source of active ingredients in ointment preparations. Lahuna leaves and binahong leaves have potential as a source of active ingredients which, based on phytochemical tests, contain flavonoids, alkaloids, saponins, tannins and steroids. Ointment preparations were made with 5 formulas based on organoleptic evaluation showing the five formulas in semi-solid form, color and characteristic odor of extracts. homogeneous and can spread evenly. Test the pH of ointment preparations according to SNI 164399-1996 for the quality of skin preparations. In vitro test showed formulas I and III had inhibition against Staphylococcus aureus ATCC 25923.